Impacts of residual insecticide spraying on the abundance and habitat occupancy of Triatoma sordida and co-occurrence with Triatoma infestans: A three-year follow-up in northeastern Argentina - Rodríguez Planes, Lucía Inés (2020)
Triatoma infestans, the main vector in the Gran Chaco region, may competitively displace other sympatric species such as Triatoma sordida. We conducted a three-year longitudinal study of site- and house-level infestation and abundance of triatomine bugs before and after an area-wide insecticide spraying campaign followed by sustained vector surveillance in a well-defined rural section of the Argentine Chaco encompassing 368–411 houses. Here, we tested whether insecticide applications targeting and virtually suppressing T. infestans reduced the abundance of T. sordida and modified its habitat occupancies, and whether their joint spatial distribution was random, aggregated or uniform, and varied over time. Systematic timed-manual searches of 18,031 sites yielded 2,226 T. sordida over seven postintervention surveys. Triatoma sordida failed to colonize human sleeping quarters after interventions, and its prime and secondary habitats remained virtually unmodified. Residual insecticide spraying and seasonality best described variations in the house-level abundance of T. sordida as determined using a generalized estimating equation model. Two-species foci occurred in 3.2% of sites ever positive for any species. The habitat-adjusted relative odds of catching one species was 10.8 times greater when the other species was present, with no evidence of heterogeneity among ORs, suggesting no antagonistic interactions throughout the follow-up. The spatial occurrence of both species was significantly aggregated within 300–500 m before and after interventions, and was random at broader spatial scales. The habitat occupancies of T. sordida may be used as a proxy for potential infestation with T. infestans and to guide targeted vector control actions.